Imaginary irishness: the feminine in dramatisations of the Paster Rising in Sean O’Casey’s the plough and the stars and Tom Murphy’s The Patriot Game - Parra, Cláudia [UNESP] (2016)
Ireland’s particular national culture has shaped an imaginary conception of identity which has also affected the image of women. Irish drama has contributed significantly to the debate on and revisionism of Irish identity and, in the twentieth century, the Easter Rising in 1916 was chosen by some Irish playwrights as a background to promote reflection on this question. Sean O’Casey and Tom Murphy presented versions of the Easter Rising on the Abbey stage which approached the identity of Irish women in a nationalistic context. A comparison of these two dramatic texts reveals that, although the playwrights used different strategies, they both reassessed the female image promoted by Irish nationalism.